Characterization of Crude Extracts from Cassia alata Linn. against Cellulitis Causing Agent Staphylococcus aureus - Toh, Seng Chiew (2019)
Cellulitis is a type of skin disease that can be found frequently from medical emergency in hospitals. The symptoms of disease begin from a small area of tenderness, followed by swelling, and redness that spreads to neighbouring parts of the skin. It can be treated by using a combination of antibiotics; however, the causing agent Staphylococcus aureus had been reported to develop resistance towards commonly used antibiotics. Furthermore, some patients are allergic towards certain antibiotics making the treatment even more difficult. Therefore, the search for an alternative, safe and cost-effective antimicrobial agent is crucial. In this study, Soxhlet extraction and maceration were utilized to produce crude extract from leaves, root and stem of Cassia alata Linn. The crude extracts were diluted and tested against S. aureus through agar-well diffusion assay, colorimetric broth microdilution and bacterial growth curve analysis. These crude extracts were further characterized through qualitative and quantitative phytochemical screenings to determine the presence of alkaloids, flavonoids, tannins and glycosides; the phenolic and flavonoid contents were quantified in the extracts. Meanwhile, the identities of phytoconstituents in the crude extracts were then identified using Gas Chromatography-Mass Spectrometry (GC-MS). From agar-well diffusion assay, root ethyl acetate Soxhlet extract showed the largest inhibition zone with an average diameter of 15.30 mm followed by leaves ethyl acetate Soxhlet extract [14.70 mm], root ethyl acetate maceration extract [13.70 mm], stem ethyl acetate Soxhlet extract [13.30 mm], leaves ethyl acetate maceration extract [13.30 mm], leaves ethanol maceration extract [13.30 mm] and stem ethyl acetate maceration extract [13.00 mm]. These crude extracts were tested in the colorimetric broth microdilution assay where the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of root ethyl acetate Soxhlet extract were identified as low as 31.25 and 62.50 µg, respectively. The MIC/MBC ratio of the C. alata Linn. extracts tested were found to be less than 4, which indicates the extracts can be utilised as the bactericidal agents. Meanwhile, the leaves hexane Soxhlet and leaves ethyl acetate maceration extract showed MIC/MBC ratio greater than 4, suggesting the potential of the extract to be utilised as the bacteriostatic agents. Apart from that, with the exemption of leaves water Soxhlet extract, most of the water extract did not show any significant inhibition effects against the S. aureus. Besides, the bacterial growth curve analysis revealed the growth pattern of the extract treated S. aureus. The application of C. alata Linn. crude extracts in this research manage to suppress the growth of S. aureus. It recorded a significant regression extension (p<0.06, p=0.00003) of lag phase for up to 6 hours after extract treatment with the increase of extract concentration. In the phytochemical screenings conducted, alkaloids were detected in all crude extracts tested while flavonoids, tannins and glycosides were only detected in eight crude extracts. Stem ethyl acetate Soxhlet and root ethyl acetate Soxhlet extract showed the highest amount of phenolic and flavonoid contents from total phenolic content (TPC) and total flavonoid content (TFC) quantitative analyses. Based on the GC-MS analysis, about 66 phytochemicals including phenolics, steroids, fatty acid, alcohol, ester and alkane hydrocarbon that possibly contributed to the antimicrobial properties were detected in the crude extracts. Hence, from this research study, the crude extracts of C. alata Linn., especially stem ethyl acetate Soxhlet, root ethyl acetate Soxhlet, stem ethyl acetate maceration and root ethyl acetate maceration extracts should be intensively studied by purification and identification of the fractions or molecules that had potential to be used as the antimicrobial agents to treat the cellulitis infection.